Propagation of the contact‐driven reduction of Mn2O3 during reactive flash sintering. Issue 12 (1st July 2019) - Murray, Shannon E.; Jensen, Tyler J.; Sulekar, Soumitra S.; Lin, Yu‐Ying; Perry, Nicola H.; Shoemaker, Daniel P.
Abstract: As the field of flash sintering expands, more diverse flash processes are emerging that exhibit complex mechanisms and kinetics. Reactive flash sintering studies have been performed using precursor oxides and have yet to explore redox reactions. We show that Mn2 O3 transforms into Mn3 O4 during stage III of flash sintering via a moving reaction front, propagating from an electrode if sufficient energy is supplied. The power density and sample temperature increases as the transformation progresses due to the lower resistivity of Mn2 O3 vs Mn3 O4, a secondary thermal runaway effect, further confirming the presence of a transformation front. Additionally, in many studies, the contact resistance is accounted for, but not utilized. The energy for the transformation may either be supplied by the contact resistance–induced Joule heating or the furnace. Room‐temperature impedance measurements demonstrate that Pt electrodes provide substantial contact resistance while Ag electrodes do not. The impedance study demonstrates that it is critical to select the appropriate electrode material to maximize or minimize contact resistance. The contact resistance may be used to create a hot spot and propagate a transformation front in any endothermic reduction reaction that occurs below 950°C in electronic conductors.